2013
DOI: 10.1097/jto.0b013e3182a7d272
|View full text |Cite
|
Sign up to set email alerts
|

Primary Salivary Gland–Type Lung Cancer: Clinicopathological Analysis of 88 Cases from China

Abstract: Salivary gland-type lung cancers are a group of low-aggressive entities with higher tendency to recurrence/metastasis. Intensive clinical, radiological, and pathological examinations are essential to estimation of the risk stratification and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 12 publications
6
105
3
Order By: Relevance
“…In our series, they were almost equally distributed. Zhu et al [4], in their experience of 88 cases, found MEC in 78.4%, ACC in 13.6% and EMC in 7.9%; while Moline et al [2] reported ACC in 64.5% and MEC in 32.3% in their experience of 62 patients of PSGTTL. Kang et al [5], in their experience of 48 cases of PSGTTL, found MEC in 54.1%, ACC in 41.7% and EMC in 4.2% Other published series focused on a particular histological type.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our series, they were almost equally distributed. Zhu et al [4], in their experience of 88 cases, found MEC in 78.4%, ACC in 13.6% and EMC in 7.9%; while Moline et al [2] reported ACC in 64.5% and MEC in 32.3% in their experience of 62 patients of PSGTTL. Kang et al [5], in their experience of 48 cases of PSGTTL, found MEC in 54.1%, ACC in 41.7% and EMC in 4.2% Other published series focused on a particular histological type.…”
Section: Discussionmentioning
confidence: 95%
“…Kang et al [5] and Molina et al [2] showed median age of involvement in MEC was younger age group than ACC , while Zhu et al [4] did not find any difference. Though all of our patients were male, previously reported case series reveal a conflicting gender predilection for PSGTTL.…”
Section: Discussionmentioning
confidence: 96%
“…A range of 2-11 cm (mean, 6.3 cm) was reported in 17 cases of salivary EMC demonstrating HGT. Pulmonary salivary gland-type tumors are detected earlier since patients experience discomfort due to the tumor's proximity with the bronchial tree (3); thus, the tumor size was smaller in these cases, ranging between 1.3 and 4.0 cm (mean, 2.5 cm) in 7 cases of pulmonary EMC (2). In addition, several previous studies have described the size of pulmonary EMCs: The size in the majority of these cases was smaller than the mean size for EMCs with HGT, as described above (3).…”
Section: Discussionmentioning
confidence: 99%
“…Primary salivary gland-type tumors of the lung account for ~0.1-1% of all primary lung carcinomas; among them, the most frequently observed histological subtype is mucoepidermoid carcinoma, followed by adenoid cystic carcinoma (1,2). Epithelial-myoepithelial carcinoma (EMC) is less common and accounts for approximately 4 and 8% of the primary salivary gland-type tumors in Korea and China, respectively (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…A few advanced bronchial MEC cases have been treated as NSCLC in clinical practice [4,14]. We summarized the papers reporting on the treatment and prognosis of pulmonary MEC (Table 1) [15][16][17][18][19][20][21][22][23][24][25][26]. Chin and colleagues examined 41 cases of surgical treatment and reported that 5-year survival rate of high-grade MEC was 53.2% and 5-year survival rate of low grade MEC was 66.7% [17].…”
Section: Discussionmentioning
confidence: 99%